Persepsi Guru dan Kendala dalam Perencanaan Pembelajaran Kurikulum Merdeka di MA Al-Islam Joresan Ponorogo: Persepsi Guru dan Kendala dalam Perencanaan Pembelajaran Kurikulum Merdeka di MA Al-Islam Joresan Ponorogo - Ayu Intan Permatasari (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
Abstract This research aims to find out about teacher perceptions in implementing Independent Curriculum learning at MA Al-Islam Joresan. The research method used is descriptive with a qualitative approach model. The research subjects were teachers, madrasa heads and students at MA Al-Islam Joresan. Data collection techniques and instruments in this research used observation techniques, interview techniques and documentation techniques. The results of the research show that teachers' perceptions regarding learning planning for the 2013 curriculum at MA Al-Islam Joresan towards the independent curriculum are quite varied. Most educators agree that the switch from the 2013 curriculum to an independent curriculum is beneficial and helps students achieve their learning goals. Even though the idea of changing the curriculum is in the good category, if teachers are not flexible and ready, then implementation will be difficult. There are several factors that become obstacles in planning Merdeka curriculum learning at MA Al-Islam Joresan, namely the quality of human resources, in this case teachers, which are still inadequate, facilities and learning resources that are still very minimal, and teachers who are not yet technologically adept This research aims to find out about teacher perceptions in implementing Independent Curriculum learning at MA Al-Islam Joresan. The research method used is descriptive with a qualitative approach model. The research subjects were teachers, madrasa heads and students at MA Al-Islam Joresan. Data collection techniques and instruments in this research used observation techniques, interview techniques and documentation techniques. The results of the research show that teachers' perceptions regarding learning planning for the 2013 curriculum at MA Al-Islam Joresan towards the independent curriculum are quite varied. Most educators agree that the switch from the 2013 curriculum to an independent curriculum is beneficial and helps students achieve their learning goals. Even though the idea of changing the curriculum is in the good category, if teachers are not flexible and ready, then implementation will be difficult. There are several factors that become obstacles in planning Merdeka curriculum learning at MA Al-Islam Joresan, namely the quality of human resources, in this case teachers, which are still inadequate, facilities and learning resources that are still very minimal, and teachers who are not yet technologically adept. Keywords Perception, Learning Planning, Independent Curriculum Abstract This research aims to find out about teacher perceptions in implementing Independent Curriculum learning at MA Al-Islam Joresan. The research method used is descriptive with a qualitative approach model. The research subjects were teachers, madrasa heads and students at MA Al-Islam Joresan. Data collection techniques and instruments in this research used observation techniques, interview techniques and documentation techniques. The results of the research show that teachers' perceptions regarding learning planning for the 2013 curriculum at MA Al-Islam Joresan towards the independent curriculum are quite varied. Most educators agree that the switch from the 2013 curriculum to an independent curriculum is beneficial and helps students achieve their learning goals. Even though the idea of changing the curriculum is in the good category, if teachers are not flexible and ready, then implementation will be difficult. There are several factors that become obstacles in planning Merdeka curriculum learning at MA Al-Islam Joresan, namely the quality of human resources, in this case teachers, which are still inadequate, facilities and learning resources that are still very minimal, and teachers who are not yet technologically adept.